Performance of various biofuel blends on burner system - Sawarimuthu, Soosai; Mohd. Jaafar, Mohammad Nazri (Faculty of Mechanical Engineering, 2008)

(untitled)
Biofuel is known as a potential replacement of fossil fuel nowadays. In Malaysia, one of the simplest ways to produce Biodiesel is mainly by blending palm oil together with conventional diesel fuel (CDF). The performance study of the Biodiesel is essential in order to justify that Biodiesel is better than CDF as fuel. The temperature profiles along the combustor have been studied in this research. The reduction of exhaust pollutants is also studied by using gas emission analysis of Biodiesel. The objective of this study is to determine the optimum blend for best performance while producing less emission compared to CDF; and also to investigate the flame pattern of the blend. The results show that Biodiesel blend of B5 perform better at stoichiometric mixture and that all the emissions of Biodiesel blends are lower than that for CDF.